If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8x + -7 = x + 1 Reorder the terms: -7 + 8x = x + 1 Reorder the terms: -7 + 8x = 1 + x Solving -7 + 8x = 1 + x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. -7 + 8x + -1x = 1 + x + -1x Combine like terms: 8x + -1x = 7x -7 + 7x = 1 + x + -1x Combine like terms: x + -1x = 0 -7 + 7x = 1 + 0 -7 + 7x = 1 Add '7' to each side of the equation. -7 + 7 + 7x = 1 + 7 Combine like terms: -7 + 7 = 0 0 + 7x = 1 + 7 7x = 1 + 7 Combine like terms: 1 + 7 = 8 7x = 8 Divide each side by '7'. x = 1.142857143 Simplifying x = 1.142857143
| 6x+6(x+15)=690 | | 4x-(9-3x)=8x-2 | | 4x^2-77x-60= | | 3y+3/8=3 | | X+7.52=9.74 | | 61-6x=12x+15 | | 4(x+2)=3(x-2) | | 7x+10-2x+20=-5 | | 4ln(x-1)=8 | | -4.7x+4.9=-4.1 | | 7y+5=-21 | | -3+4-6x+8+x=40 | | 3-31=w | | 0x+0y=8 | | 8(5-3z)=29-22z | | 5x^2+15x+45=0 | | 5x+19=15x-51 | | 6+7+5uv= | | 6w-12=17 | | 23=m+1 | | 7x-4(x-2)=33 | | 4x-12=-12+4x | | 3m-10=2(4m-s) | | 79-5x=31x+15 | | x=173+173 | | 5/2(w-1)=15 | | 2xy(3x+2)-4xy(x+4)= | | 5.4q-4.9-5.8q=1.4q-3.3 | | m-8n+m+8n= | | 5.4q-4.9-5.8q=-1.4q-3.3 | | 2x+1x+5= | | 76a^2+34a+4=0 |